2022
DOI: 10.3389/fpsyt.2022.1022881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of burnout among stay-behind healthcare workers during the current Omicron wave of COVID-19 in Taizhou, China

Abstract: BackgroundSince February 2022, a new Omicron wave of COVID-19 emerged in Shanghai, China. Many healthcare workers came to Shanghai from hospitals of other parts of China as aid workers. Hospitals in areas with mild COVID-19 outbreaks will inevitably be understaffed, it is likely to cause job burnout of stay-behind healthcare workers. Stay-behind healthcare workers were those who had not been dispatched to support COVID-19 prevention and control in other regions. This study was designed to evaluate the burnout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(41 reference statements)
3
7
0
Order By: Relevance
“…SARS-CoV-2 infection and its management by healthcare management systems remains a matter of significant concern. Omicron, the current SARS-CoV-2 variant, which includes BA.1, BA.2, BA.3, BA.4, BA.5, and descendent lineages, is much more contagious than its predecessors [25,26], which means that during surges, without an adequate level of preparedness, hospitals can become understaffed, thereby stressing and overburdening healthcare workers to a greater degree [27]. Healthcare workers are defined as workers who deliver care and services to the sick and ailing either directly (e.g., physicians, nurses, healthcare assistants, midwifes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 infection and its management by healthcare management systems remains a matter of significant concern. Omicron, the current SARS-CoV-2 variant, which includes BA.1, BA.2, BA.3, BA.4, BA.5, and descendent lineages, is much more contagious than its predecessors [25,26], which means that during surges, without an adequate level of preparedness, hospitals can become understaffed, thereby stressing and overburdening healthcare workers to a greater degree [27]. Healthcare workers are defined as workers who deliver care and services to the sick and ailing either directly (e.g., physicians, nurses, healthcare assistants, midwifes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 displayed 10 articles related to the effect of social support on burnout with high AOR values found in the study of Pan et al (2022) (aOR = 0.94; 95% CI = 0.91 to 0.98) and the lowest aOR value found in the study by Belay et al ( 2021) (aOR= 0.07; 95% CI= 0.02 to 0.25). Table 4.…”
Section: Resultsmentioning
confidence: 98%
“…According to the results of binary logistic regression analysis, nurses with intermediate and senior professional titles presented lower levels of burnout, which was consistent with the findings in prior research (Jiang et al, 2021 ). Pan and colleagues investigated the burnout among stay-behind healthcare workers in the current COVID-19 Omicron wave in Taizhou, China (Pan et al, 2022 ). They found that professional title appeared to be significantly related to severe burnout.…”
Section: Discussionmentioning
confidence: 99%